Innovative Breast Massager Tool with 3-Movement Method - Nisrina, Safira Fegi; Sari, Cempaka Kumala (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Mother's Milk (ASI) is nutritious food for babies up to 6 months, but it is also recommended that breast milk be given to babies up to 2 years old. The benefits of breastfeeding include for antibodies in infants, avoiding allergic diseases, avoiding the risk of diseases of the respiratory tract, reducing diarrhea, reducing diabetes, and others. The problems that occur in Indonesia are several things, namely the limitations of exclusive breastfeeding due to the lack of knowledge of mothers about breast care and the lack of use of breast care in breast care for breastfeeding mothers. This can have a negative impact from not doing breast care or breast care which can have a negative impact, one of which is mastitis or tissue problems in the breast. One of the efforts to get sufficient milk production is that mothers must routinely carry out breast care, namely the use of a Breast Care tool design for the lactation process. Breast massage device or Breast Care for the lactation process can be used when mothers experience breastfeeding problems, with vibrations generated from servo motors and control motors on the device so that it can produce 3 types of vibrations that nursing mothers can use during breastfeeding.